2021
DOI: 10.1016/j.isci.2021.103284
|View full text |Cite
|
Sign up to set email alerts
|

A wireless optoelectronic skin patch for light delivery and thermal monitoring

Abstract: Summary Wearable optoelectronic devices can interface with the skin for applications in continuous health monitoring and light-based therapy. Measurement of the thermal effect of light on skin is often critical to track physiological parameters and control light delivery. However, accurate measurement of light-induced thermal effects is challenging because conventional sensors cannot be placed on the skin without obstructing light delivery. Here, we report a wearable optoelectronic patch integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…[29][30][31] Recently, a functionalized poly(acrylamide)-based hydrogel was used to formulate a soft interface between wearable electronic devices and human skin, 32 i.e., poly(3,4-ethylenedioxythiophene) (PEDOT)-reinforced laser-irradiated graphene as hetero-structured 3D transducers in a flexible skin patch biosensor. 33 Many advanced skin patches such as pulse oximetry sensing patches with ultralow power consumption, 34 multifunctional hybrid skin patches, 35 textile sensor patches for sweat analysis, 36,37 stress monitoring patches, 38 blood pressure sensing patches, 8 self-powered smart patches, 39 and optoelectronic skin patch 40 have been successfully produced. A PubMed® and EspaceNET search for the term "electronic skin patches" in the title/abstract of peer-review papers demonstrated the exponential increase in the research over the past ten years into the development of these versatile materials for biomedical applications (Fig.…”
Section: Yang LImentioning
confidence: 99%
“…[29][30][31] Recently, a functionalized poly(acrylamide)-based hydrogel was used to formulate a soft interface between wearable electronic devices and human skin, 32 i.e., poly(3,4-ethylenedioxythiophene) (PEDOT)-reinforced laser-irradiated graphene as hetero-structured 3D transducers in a flexible skin patch biosensor. 33 Many advanced skin patches such as pulse oximetry sensing patches with ultralow power consumption, 34 multifunctional hybrid skin patches, 35 textile sensor patches for sweat analysis, 36,37 stress monitoring patches, 38 blood pressure sensing patches, 8 self-powered smart patches, 39 and optoelectronic skin patch 40 have been successfully produced. A PubMed® and EspaceNET search for the term "electronic skin patches" in the title/abstract of peer-review papers demonstrated the exponential increase in the research over the past ten years into the development of these versatile materials for biomedical applications (Fig.…”
Section: Yang LImentioning
confidence: 99%
“…Flexible and wearable electronic devices have drawn enormous attention in various fields such as touch panels, transparent heaters, health monitoring sensors, air filters, fuel cells, supercapacitors, and color changing soft robotics. , Among several candidates to build such devices, silver nanowires (AgNWs) are generally considered to hold great potential to achieve excellent optical, electrical, and mechanical performance. As a basic component, transparent conductive electrodes (TCEs) made of AgNWs are now reportedly to show higher transmittance and lower sheet resistance than commercial TCEs made of indium tin oxide (ITO) ,, and much better resistance against damage caused by deformation like bending and stretching. Bulk copper is much cheaper than silver, and applications including TCEs, touch panels, solar cells, and wearable heaters based on copper nanowires (CuNWs) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This preliminary study on light-controlled inhibition of the coppercontaining enzyme showed unequivocally that adverse effects resulting from the removal of metal centers from metalloenzymes can be avoided when the photocaged chelators are activated locally by light. Tissue-implantable and wirelessly programmable optoelectronic devices were developed by Ho and co-workers 24,25 and it was shown that these devices can be used to selectively and locally activate various light-sensitive molecules including our studied photocaged chelators in target tissues or organs.…”
mentioning
confidence: 99%